Exploring the Essence of the Rise of Motion Comics in the Information Age - Zeng, Zhiyong (Journal of Theory and Practice of Social Science, 2023)
This article explores the essence of the rise of Motion comics by analyzing the historical background and technological conditions. In recent years, with the rapid development of mobile internet, the animation industry has also ushered in unprecedented development opportunities, with "Motion comics" characterized by short, flat, and fast gradually developing and growing. However, for a long time, people have had a vague understanding of Motion comics, only seeing them as a product of the fusion of old- fashioned animation and comics. However, this article proposes a different viewpoint. In the article, dynamic comics are a unique form of animation rooted in the decline of traditional animation and comics, and are rooted in the emergence of information technology. The article innovatively proposes that Motion comics are developed based on strip-type comics, the technology of Motion Graphics, and short videos.